Essential Update 2023/2024: Multidisciplinary Treatment for Invasive Intraductal Papillary Mucinous Carcinoma - Seiko Hirono (Annals of Gastroenterological Surgery, 2025)
ABSTRACT Invasive intraductal papillary mucinous carcinoma (IPMC) has a high malignant potential, with surgical resection being the only potentially curative treatment. However, even after surgical resection, recurrence occurs frequently and the prognosis is poor once recurrence develops. While retrospective studies aiming to achieve long‐term survival in invasive IPMC patients have been reported, the rarity of invasive IPMC has resulted in small‐scale datasets, leading to low levels of evidence. Consequently, the utility of adjuvant therapy after surgery, neoadjuvant therapy (NAT) before surgery, and treatments for postoperative recurrence in invasive IPMC remains unclear, with treatment strategies varying by institution—ranging from surgical resection alone to approaches based on conventional pancreatic cancer treatment. Recently, several large‐scale multicenter studies on invasive IPMC have been reported. These studies suggested that while adjuvant therapy after surgery may not be beneficial for all invasive IPMC patients, it could potentially extend survival in cases with advanced‐stage disease. Regarding NAT before surgery for invasive IPMC, the number of reported cases is extremely limited, and no definitive evidence has been established. For postoperative recurrence of invasive IPMC, some studies have indicated that administering treatment may prolong survival. Although these large‐scale studies have gradually clarified certain characteristics of invasive IPMC, they are all retrospective in nature, resulting in a low level of evidence. To achieve long‐term survival for invasive IPMC patients, large‐scale prospective multicenter studies are needed in the future.